Burnout and Teachers’ Job Satisfaction in Public Secondary Schools in Anambra State - Alaebo, Lynda Oluomachukwu; Nwosu, Kingsley Chinaza (Journal of Research in Industrial Technology and Educational Studies, 2025)
This study used a correlational research design to establish how burnout is associated with teachers’ job satisfaction. Two research questions and two null hypotheses guided the study. The sample for the study consisted of 752 teachers drawn from the population of the study using a multi-stage random sampling procedure. An instrument consisting of burnout Assessment Scale (BAS) and Teacher Job Satisfaction Scale (TJSSS) was used for data collection. Data collected were analyzed using Pearson Product Moment Correlation and regression analysis. One of findings of the study revealed a moderate negative relationship between burnout and job satisfaction in public secondary schools in Anambra State. Based on the findings of the study, it was recommended among others, that principals and teachers should take proactive measures to manage burnout effectively.